A perspective for reducing sugar consumption, encouraging healthier eating habits, and enhancing public wellness - Choudhary, Neha; Biswas, Riya R.; Arya , Ankur (International Journal Of Community Medicine And Public Health, 2025)
Sugar, sugar sweetened beverages (SSBs) and food items high in fat, salt and sugar (HFSS) are important contributors to the rising burden of non-communicable diseases worldwide. Global evidence suggests a linkage of habitual intake of SSBs with overweight and obesity, and a higher risk of type 2 diabetes mellitus, cardiovascular diseases and some cancers, as compared to infrequent SSB consumption. This makes these beverages a clear target for policy and regulatory actions. While over 70 countries are using ‘sin’ tax as an effective tool for reducing consumption of sugar, SSBs and HFSS, the existing goods and service tax (GST) in India does not differentiate between healthy and unhealthy beverages. A growing body of available and emerging evidence and country experiences indicate that ‘health tax’ (HT) on sugar, SSBs and HFSS are an effective tool to reduce consumption, with the potential to improve health without hampering nation’s revenue generation; in fact, it could aid in its generation. This viewpoint provides an update on the evidence linking High taxation on sugar, SSBs, HFSS on health demands and revenue and ultimately on health benefits.